In vitro dose effect relationships of actinium-225- and lutetium-177-labeled PSMA-I&T. - Ruigrok, Eline A. M.; Tamborino, Giulia; de Blois, Erik; Roobol, Stefan J.; Verkaik, Nicole; De Saint-Hubert, Marijke; Konijnenberg, Mark W.; van Weerden, Wytske M.; de Jong, Marion; Nonnekens, Julie (European Journal of Nuclear Medicine & Molecular Imaging, 2022)
Purpose: Targeting the prostate-specific membrane antigen (PSMA) using lutetium-177-labeled PSMA-specific tracers has become a very promising novel therapy option for prostate cancer (PCa). The efficacy of this therapy might be further improved by replacing the β-emitting lutetium-177 with the α-emitting actinium-225. Actinium-225 is thought to have a higher therapeutic efficacy due to the high linear energy transfer (LET) of the emitted α-particles, which can increase the amount and complexity of the therapy induced DNA double strand breaks (DSBs). Here we evaluated the relative biological effectiveness of [225Ac]Ac-PSMA-I&T and [177Lu]Lu-PSMA-I&T by assessing in vitro binding characteristics, dosimetry, and therapeutic efficacy. Methods and results: The PSMA-expressing PCa cell line PC3-PIP was used for all in vitro assays. First, binding and displacement assays were performed, which revealed similar binding characteristics between [225Ac]Ac-PSMA-I&T and [177Lu]Lu-PSMA-I&T. Next, the assessment of the number of 53BP1 foci, a marker for the number of DNA double strand breaks (DSBs), showed that cells treated with [225Ac]Ac-PSMA-I&T had slower DSB repair kinetics compared to cells treated with [177Lu]Lu-PSMA-I&T. Additionally, clonogenic survival assays showed that specific targeting with [225Ac]Ac-PSMA-I&T and [177Lu]Lu-PSMA-I&T caused a dose-dependent decrease in survival. Lastly, after dosimetric assessment, the relative biological effectiveness (RBE) of [225Ac]Ac-PSMA-I&T was found to be 4.2 times higher compared to [177Lu]Lu-PSMA-I&T. Conclusion: We found that labeling of PSMA-I&T with lutetium-177 or actinium-225 resulted in similar in vitro binding characteristics, indicating that the distinct biological effects observed in this study are not caused by a difference in uptake of the two tracers. The slower repair kinetics of [225Ac]Ac-PSMA-I&T compared to [177Lu]Lu-PSMA-I&T correlates to the assumption that irradiation with actinium-225 causes more complex, more difficult to repair DSBs compared to lutetium-177 irradiation. Furthermore, the higher RBE of [225Ac]Ac-PSMA-I&T compared to [177Lu]Lu-PSMA-I&T underlines the therapeutic potential for the treatment of PCa.